ANALISIS FAKTOR-FAKTOR YANG MEMEPENGARUHI MINAT MAHASISWA BERWIRAUSAHA - Saputri, Novitasari Agus (Jurnal Inovasi Ekonomi, 2019)
The purpose of this study is to determine the factors that influence student interest in entrepreneurship. This study uses qualitative research, the sample used is accounting students who have entrepreneurship both in the fields of services, trade and manufacturing. The results of this study indicate that there are four factors that influence student interest in entrepreneurship. These factors are profit generated, freedom in work, personal dreams and independence.